2005
DOI: 10.1177/00222194050380050701
|View full text |Cite
|
Sign up to set email alerts
|

Layers of Reading Intervention in Kindergarten Through Third Grade

Abstract: In this study, students and their teachers participated in a layered approach to reading intervention in kindergarten through third grade that included professional development for teachers in scientifically based reading instruction, ongoing measurement of reading progress, and additional small-group or individual instruction for students whose progress was insufficient to maintain grade-level reading achievement. Reading outcomes were compared with historical control groups of students in the same schools. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 39 publications
7
107
2
3
Order By: Relevance
“…However, students with disabilities are a subgroup whose performance has historically been observed to be significantly discrepant from peers. Given the effects of early intervention to improve educational outcomes (Denton and Mathes 2003;O'Connor et al 2005;Simmons et al 2008) and the need for students to be identified early in order to maximally benefit from intervention (Cavanaugh et al 2004;Vellutino et al 2006), it is clear that universal screening practices are essential for identifying students with LD early.…”
Section: Universal Screeningmentioning
confidence: 99%
“…However, students with disabilities are a subgroup whose performance has historically been observed to be significantly discrepant from peers. Given the effects of early intervention to improve educational outcomes (Denton and Mathes 2003;O'Connor et al 2005;Simmons et al 2008) and the need for students to be identified early in order to maximally benefit from intervention (Cavanaugh et al 2004;Vellutino et al 2006), it is clear that universal screening practices are essential for identifying students with LD early.…”
Section: Universal Screeningmentioning
confidence: 99%
“…It is important for teachers to receive adequate training so they are able to replicate research conditions. This training should include proper pronunciation of sounds in isolation and how to model blending and segmenting clearly and correctly (O'Connor, Fulmer, Harty, & Bell, 2005 ). Techniques commonly used by researchers include stretching continuous sounds when modeling how to blend, following a model-lead-test procedure during activities, and providing differentiated instruction.…”
Section: Components Of Phonological Awareness Interventionmentioning
confidence: 99%
“…However, relying on predictions made within 1-2 years of responsivenessgroup formation fails to address group instability, which primarily occurs during 1 st and 2 nd grade (O'Connor, Fulmer, Harty, & Bell, 2005;Simmons et al, 2008). Furthermore, RtI responsiveness indicators collected in 1 st and 2 nd grade and used to predict RD in these same grades may not help to identify those students who perform well on early RtI assessments, but…”
Section: Intervention Responsiveness As An Indicator Of Continued Riskmentioning
confidence: 99%